International authorship in leading world journals on incontinence and pelvic floor disorders: Is it truly international?. (October 2019) - Najjar, Wassim; Mouanness, Marco Abdo; Rameh, Georges; Bazi, Tony
Abstract: Objective: The primary aim of this study is to compare the authorship in the Journal of Neurourology and Urodynamics (NAU) and the International Urogynecology Journal (IUJ) across two categories: country members of the Organization for Economic Co-operation and Development (OECD) and non-members of OECD (non-OECD). The secondary aim is to explore the obstacles in publishing in these two journals. Study design: NAU and IUJ articles between June 2014 and June 2018 were manually screened and divided into 2 categories depending on the country of affiliation of the corresponding author: OECD versus non-OECD. They were then divided into seven different types depending on the scope of the article. An online anonymous lime survey was then used to get the opinions of corresponding authors from non-OECD countries regarding obstacles to publishing. Results: The OECD countries, representing 17.0% of the world population contributed to 85.4% of the 1885 articles evaluated, whereas only 14.6% originated from non-OECD countries. The distribution of the article types was comparable between the 2 groups. Out of 194 corresponding authors from non-OECD countries, 35 (18.7%) returned a completely filled survey that could be included in the analysis. Lack of funding, language barrier, and perceived bias were acknowledged as barriers to research and publishing. The majority of corresponding authors believed that international collaboration can improve the quality of research. Conclusions: The majority of NAU and IUJ articles originate from countries belonging to the OECD group. The uneven representation could be due to gaps in research activity, to obstacles in submission or both.